Purificação e caracterização bioquímica de três proteases presentes nas peçonhas de Bothrops alternatus e Bothrops moojeni: balt-f1, balt-f2 e bmoo-f - Costa, Júnia de Oliveira (2004)
This work describes the purification and partial biochemical characterization of two proteases from Bothrops alternatus venoms (Balt-F1 and Balt-F2) and one from Bothrops moojeni (Bmoo-F). The enzymes were purified on chromatographic columns containing the DEAE Sephacel, Sephadex G-75 and Heparin-Agarose resins. The apparent molecular weight analyzed in SDS-PAGE under reducing conditions, showed homogeneous bands of 26,200, 29,900 and 24,800, respectively. All enzymes hydrolyzed bovine fibrinogen A-a and B-p chains. Balt-F1 did not show coagulating and defibrinogenating activities. The enzymes Balt-F2 and Bmoo-F, when injected i.p. made the blood of mice uncoagulable. The inhibition of proteolytic activity on bovine fibrinogen from the enzymes Balt-F1, Balt-F2 and Bmoo-F by metal ion chelating agents, allows them to be classified as metalloproteases.